The quest of modernism in the 19th century Japan: an assessment - Mansor Majdin, Mohamad Firdaus (2020)
This paper will deal with the process of modernization of Japan with particular reference to important elements of Japanese pursuits of modernization at the expense of growing Western penetration into the country. This will specifically deal with the Meiji Restoration where process of modernization has taken place. Furthermore, there will be a discussion on the efforts of Japanese statesmen in their attempts to modernize several aspects of vital institutions in Japan as well as issues concerning the modernization encountered by the Japanese statesmen in the country. Sources for this analysis will be taken from studies of both Western writers and inside writers on modernization in Japan. The ability of Japanese statesmen to adopt and adapt foreign practices which later infused with local circumstances suggest that they are capable of modernizing their country by their own rights.